GROUND MOTION IN YOGYAKARTA CITY, YOGYAKARTA SPECIAL PROVINCE, INDONESIA ON DENSELY MICROTREMOR OBSERVATIONS AND SHEAR WAVE VELOCITY - Zaw Lin Kyaw; Subagyo Pramumijoyo; Salahuddin Husein; Teuku Faisal Fathani; Junji Kiyono (Geological Engineering Department Universitas Gadjah Mada, 2015)
Microtremor is currently considered the foremost tool in site effect studies. The ground motion is estimated with microtremor observations, meaning that subsoil mechanical properties and geometry are evaluated and from them an estimate of local amplification is computed. Here, the ground motion is studied by the site effects of seismic hazard zonation of urban areas in Yogyakarta City. The main purpose of this paper is zoning the geological engineering features and assessing seismic of the research urban area. In this regard, the microtremors are measured at 274 sites by single station sampling method and Nakamura technique. The microtremors of all over the city are processed by a model of Mitutoyo-GPL-6A3P. The amplification factor generally ranges between 0.70 and 5.56 and the natural frequency normally varies between 0.40 and 3.30 Hz. The information layers are prepared in GMT used for detecting the zonation of potential seismic hazard. The shear wave velocity is calculated in 12 existing drilling sites based on the geotechnical approach of SPT for soil condition. To study the ground motion, geological engineering condition is investigated using amplification factor, natural frequency, shear wave velocity maps which are analyzed using densely single microtremor observation and SPT from existing drilling sites. Keywords: Ground motion, amplification factors, natural frequency; H/V spectral ratio, microtremor observations, Yogyakarta Urban